2014
DOI: 10.4271/2014-01-2826
|View full text |Cite
|
Sign up to set email alerts
|

On-Road and Chassis Dynamometer Evaluations of Emissions from Two Euro 6 Diesel Vehicles

Abstract: Euro 6, the next stage of European emissions regulations for light-duty vehicles, becomes mandatory from 1 September 2014 for the Type Approval of new passenger cars and the smaller light commercial vehicles (categories M and N1 Class 1), and 1 year later for all other commercial vehicles not exceeding 3.5 tonnes maximum mass (categories N1 Class II and N1 Class III). One year after these dates, Euro 6 becomes mandatory for all new registrations. A number of papers and reports have raised concerns over the emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 6 publications
10
48
0
1
Order By: Relevance
“…Bergmann et al (2009) measured lower emissions in the laboratory compared to on-road tests for a DPF equipped light-duty vehicle. Similarly, Andersson et al (2014) found almost one order of magnitude lower SPN emissions in the laboratory than on the road with PEMS for DPF-equipped diesel cars. These results are in agreement with our findings.…”
Section: Literature Overview On Comparisons Between Laboratory and Onmentioning
confidence: 73%
See 3 more Smart Citations
“…Bergmann et al (2009) measured lower emissions in the laboratory compared to on-road tests for a DPF equipped light-duty vehicle. Similarly, Andersson et al (2014) found almost one order of magnitude lower SPN emissions in the laboratory than on the road with PEMS for DPF-equipped diesel cars. These results are in agreement with our findings.…”
Section: Literature Overview On Comparisons Between Laboratory and Onmentioning
confidence: 73%
“…One particular issue of mobile SPN measurements refers to emissions sampling directly from the tailpipe; the resulting SPN counts might not be identical to those measured by following the regulated procedure at the full dilution tunnel that alters particle properties due to e.g., coagulation, thermophoresis, diffusion etc. Comparisons of PEMS-SPN with reference PMP systems, especially during on-board operation, as well as of emissions of vehicles both in the laboratory and during on-road driving are still scarce (e.g., Merkisz et al, 2009;Andersson et al, 2014). Quite often high differences between laboratory and onroad testing are found (Andersson et al, 2014).…”
Section: Background Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…These models are built using data collected from vehicle emission measurement experiments. Various methods are used to quantify vehicle emissions, including chassis dynamometer tests under controlled conditions (Schmitz et al, 2000;Caplain et al, 2006;Livingston et al, 2009;Adam et al, 2011;Forestieri et al, 2013;Alves et al, 2015;Yang et al, 2015;Louis et al, 2016) and real-world measurements such as tunnel studies, remote sensing and on-road tests (Chan et al, 2004;Kristensson et al, 2004;Chan and Ning, 2005;Jiang et al, 2005;Ko and Cho, 2006;Zavala et al, 2006;Chen et al, 2007;Ho et al, 2009;Wehner et al, 2009;Liu et al, 2010;Rubino et al, 2010;Andersson et al, 2014;Banitalebi et al, 2016). As described by Franco (2013), real-world measurements can be used to monitor a host of vehicle emissions under real driving conditions.…”
Section: Introductionmentioning
confidence: 99%